A two-dimensional photonic crystal hydrogel biosensor for colorimetric detection of penicillin G and penicillinase inhibitors. Issue 2 (19th November 2020) - Wang, Changping; Xiao, Fubing; Chen, Qianshan; Wang, Shihong; Zhou, Jun; Wu, Zhaoyang
Abstract : A simple 2DPPCH biosensor was developed for colorimetric detection of penicillin G and penicillinase inhibitors based on the enzymatic hydrolysis reaction between penicillin G and penicillinase. Abstract : A simple penicillinase functionalized two-dimensional photonic crystal hydrogel (2DPPCH) biosensor was developed for colorimetric detection of penicillin G and penicillinase inhibitors. The penicillinase can specifically recognize penicillin G and catalyze it to produce penicilloic acid, which decreases the pH of the hydrogel microenvironment and shrinks the pH-sensitive hydrogel. The particle spacing decrease of the 2D photonic crystal array induced by the hydrogel shrinkage further causes a blue-shift in the diffraction wavelength. While the hydrolysis reaction is repressed upon treatment with clavulanate potassium (a kind of penicillinase inhibitor), no significant change in the diffraction wavelength is found. The detection of targets can be achieved by measuring the Debye diffraction ring diameter or observing the structural color change in the visible region. The lowest detectable concentrations for penicillin G and clavulanate potassium are 1 μM and 0.1 μM, respectively. Moreover, the 2DPPCH is proved to exhibit high selectivity and an excellent regeneration property, and it shows satisfactory performance for penicillin G analysis in real water samples.